Legal Enforcement for Limited Companies that Do Not Implement Corporate Social Responsibility - Pratiwi, Agustina Ni Made Ayu Darma; Windia, I Wayan; Widiatedja, I Gusti Ngurah Parikesit; Resen, Made Gde Subha Karma (Formosa Journal of Multidisciplinary Research, 2024)
Supporting the Company's business activities, CSR must be implemented not only as an implementation of responsibility but also as an obligation for the business world. CSR can be said to be future savings for companies to gain profits. The benefits obtained are not just financial benefits but more on the trust of the surrounding community and stakeholders based on the principles of volunteerism and partnership. The formulation of the problem in this research is how to enforce the law for Limited Liability Companies that do not implement Corporate Social Responsibility. This research uses a normative type of research. The results of this research are that Limited Liability Companies have an obligation to implement CSR. However, if a Limited Liability Company does not implement CSR, there are no legal sanctions related to Limited Liability Companies that do not implement CSR. If there are no regulations that enforce it, many companies will ignore CSR provisions and this will become an obstacle in the future in implementing CSR.